(untitled) (Research, Society and Development, 2024)
The palate is the structure that forms the roof of the oral cavity, separating it from the nasal cavity. However, during embryonic development, the palate may not close completely, resulting in an abnormal opening between these cavities. This condition is known as cleft palate or palatoschisis, a congenital malformation that affects several animals, including dogs and cats. Based on this, this work aims to anatomically describe the palate, as well as present the anatomical changes associated with the cleft palate, correlating with the clinical implications of this condition on the health of dogs and cats through a literature review. Although the exact etiology is not yet fully elucidated, it is believed that genetic and environmental factors may play an important role in the development of this condition. Clinical signs of cleft palate in dogs and cats include difficulty nursing, choking, coughing, sneezing, nasal discharge, aspiration pneumonia, and poor weight gain. Diagnosis is based on physical examination, with visual inspection of the oral cavity, and can be confirmed through imaging exams such as X-rays and computed tomography. Treatment of cleft palate in dogs and cats generally involves surgical intervention to close the cleft, aiming to restore the separation between the oral and nasal cavities. The prognosis depends on the extent of the cleft, the presence of other associated malformations, and the age of the animal at the time of surgery, but with appropriate treatment and postoperative care, many cats with cleft palate can have a good quality of life.